Mechanism and Kinetics of SO2 Poisoning on the Electrochemical Activity of La0.8Sr0.2MnO3 Cathodes of Solid Oxide Fuel Cells - Wang, Cheng Cheng; Chen, Kongfa; Jiang, San Ping (The Electrochemical Society, Inc, 2016)
The effect of sulfur deposition and poisoning on the electrochemical activity of La0.8Sr0.2MnO3 (LSM) cathode of solid oxide fuel cells (SOFCs) for the O2 reduction reaction is investigated. Sulfur poisoning of the electrochemical activity of LSM electrodes is characterized by two-stage degradation processes: initial rapid degradation by the adsorbed SO2 on the surface of LSM electrodes, inhibiting the dissociation adsorption and diffusion processes of oxygen, followed by a slow degradation due to the deposition and formation of SrSO4 on the LSM electrode surface and at the three phase boundaries. The degradation due to the adsorption of SO2 is largely reversible and characterized by the initial rapid increase of polarization potential, ?E. The ?E for the O2 reduction reaction at 800°C is significantly smaller than that for the reaction at 700°C in the presence of 1 ppm and 10 ppm SO2 in air due to the reduced adsorption of SO2 on LSM electrode surface. However, the sulfur deposition and poisoning on the LSM cathodes is not reversible as the result of the formation of SrSO4, which in turn accelerates the Sr segregation and consequently depletes Sr content at the A-site of LSM, leading to the significant degradation of the electrochemical activity of LSM electrodes. The sulfur deposition process is most likely controlled by the nucleation reaction between gaseous SO2 and segregated SrO, forming SrSO4.